Enhanced susceptibility to oiling may limit denitrification recovery in marshes subjected to woody encroachment - Tatariw, Corianne; Mortazavi, Behzad; Flournoy, Nikaela; Kleinhuizen, Alice A.; Crawford, Patrice; Overton, Edward B.; Sobecky, Patricia A. (Frontiers in Environmental Science, 2022)
Salt marshes provide valuable ecosystem services but are subjected to concomitant stressors that may impact their ability to provide those services. Climate change has led to the poleward expansion of mangroves into salt marshes globally. In the northern Gulf of Mexico, warming winter temperatures have resulted in the expansion of Avicennia germinans (black mangrove) into forb-dominated salt marshes, resulting ecosystem structure shifts that can impact ecosystem services, including biogeochemical processes such as nitrogen removal. We conducted a field study to assess the impact of woody encroachment in mediating biogeochemical recovery 7—8 years after the Deepwater Horizon oil spill. We collected sediments from S. alterniflora and A. germinans dominated plots in the Chandeleur Islands (LA, USA), a chain of barrier islands in the northern Gulf of Mexico subjected to a range of oiling following the spill. We compared nitrate reduction rates (denitrification and dissimilatory nitrate reduction to ammonium), microbial community composition, and denitrifier marker gene abundance at sites subjected to light and moderate oiling using a combination of isotope pairing on sediment slurries, 16S sequencing, and qPCR. We predicted that overall, denitrification rates and microbial functional capacity would be enhanced in mangrove dominated sediments. We also predicted that these enhancements would be diminished at the more intensely oiled site due to higher susceptibility of A. germinans to oiling. Denitrification potential rates were higher in mangrove sediments at the lightly oiled site, whereas dissimilatory nitrate reduction to ammonium potential rates were higher in marsh sediments. Indicator analysis selected putative sulfur cycling taxa as indicators of marsh sediments, suggesting that changes in oxygen availability associated with encroachment may be driving the differences in process rates. There was no difference in process rates between plant types at the moderately oiled site, where heavily weathered oil residue was still present. Sediment nutrient stocks were lower in moderately oiled mangrove plots compared to lightly oiled mangrove plots, suggesting sediment fertility recovery following the spill may have been slower in the mangroves. This study shows that woody encroachment can impact both biogeochemical services that marshes provide and their response to and recovery from disturbances.